2016
DOI: 10.1007/s10616-016-0014-y
|View full text |Cite
|
Sign up to set email alerts
|

Cell cycle arrest and mechanism of apoptosis induction in H400 oral cancer cells in response to Damnacanthal and Nordamnacanthal isolated from Morinda citrifolia

Abstract: Oral cancer is the eleventh most prevalent cancer worldwide. The most prevalent oral cancer is oral squamous cell carcinoma (OSCC). Damnacanthal (DAM) and nordamnacanthal (NDAM), the anthraquinone compounds, are isolated from the root of Morinda citrifolia L. (Noni), which has been used for the treatment of several chronic diseases including cancer. The objectives of this study were to evaluate the cytotoxicity, cell death mode, cell cycle, and the molecular mechanism of apoptosis induced by DAM and NDAM on OS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 35 publications
1
8
0
3
Order By: Relevance
“…The morphological changes in CPT-CEF treated HT29 and A549 cells were characterised using acridine orange (AO) and propidium iodide (PI) double staining, according to the method described by Hajiaghaalipour et al . 46 , 47 with minor modifications. Briefly, cells were plated at a density of 1 × 10 5 cells/mL in a six-well plate and treated with the IC 50 concentration of CPT-CEF in an atmosphere of 5% CO 2 at 37 °C for 48 h. The cells were then trypsinized with trypsin-EDTA, washed twice with PBS and centrifuged for 5 min to remove the remaining media.…”
Section: Biological Application Studiesmentioning
confidence: 99%
“…The morphological changes in CPT-CEF treated HT29 and A549 cells were characterised using acridine orange (AO) and propidium iodide (PI) double staining, according to the method described by Hajiaghaalipour et al . 46 , 47 with minor modifications. Briefly, cells were plated at a density of 1 × 10 5 cells/mL in a six-well plate and treated with the IC 50 concentration of CPT-CEF in an atmosphere of 5% CO 2 at 37 °C for 48 h. The cells were then trypsinized with trypsin-EDTA, washed twice with PBS and centrifuged for 5 min to remove the remaining media.…”
Section: Biological Application Studiesmentioning
confidence: 99%
“…1)is a derivative of Damnacanthus (a flowering plant of the Rubiaceae family native to eastern Asia), and has been demonstrated to exhibit potent anticancer properties (9). Previous studies have demonstrated that the compound exhibits cytotoxic activity and anticancer cell proliferation effects, which may result in the apoptosis of cancer cells and an antitumor function (8,10). The aim of the present study was to investigate the…”
Section: Introductionmentioning
confidence: 99%
“…[ 40 ] The cell apoptosis under different treatments was evaluated by flow cytometry analysis using fluorescein isothiocyanate‐annexin V/propidium iodide (PI) double staining. [ 41 ] As shown in Figure 3c, the percentage of apoptotic cells was ≈0.35% for the normal group, while the H 2 O 2 group showed up to 44.28% of cell apoptosis rate. In comparison, the cell apoptosis rates pretreated with 200 µg mL −1 of MICH VE – and MICH were found to be 5.64% and 4.90%, respectively.…”
Section: Resultsmentioning
confidence: 96%